Guía para la aplicabilidad de habilidades gerenciales eficientes en una empresa constructora (2023)
Hard and soft skills are a fundamental factor in decision-making and in construction companies, a bad decision leads to delays in the execution of projects, monetary losses, low returns, among others. The manager is a figure with extensive experience and certain skills that he has acquired during his work career, which is why he in turn has great responsibility when making decisions that can lead to the success or failure of the company. At the moment of making decisions is where the skills come into action since these are part of their profile and experience, which leads to them having leadership, coexistence, negotiation, follow-up skills, among others; and so, depending on the decision that must be made, correctly use the respective ability so as not to make decisions based on assumptions that, although they may be favorable, in turn become the cause of problems in the future.